KETIDAKADILAN GENDER DALAM SISTEM WANGSA - Sudantra, I Ketut (Jurnal Studi Jender SRIKANDI, 2007)
The tribe system in Bali called as Wangsa contains the injustice of gender. Inthe wangsa system, there is a principle forbiding a girl to be married with a boy from lower class status; on the other hand that prohibition does not prevailed for the boy. The prohibition is called as asupundung and alangkahi karang hulu.